Establishing the Genotyping Method for NAT2 Polymorphism in Vietnamese Tuberculoma Patients - Pham, Thi Hong Nhung (H. : ĐHQGHN, 2019)
The metabolism of Isoniazid, one of the first-line antituberculosis drugs for TB treatment and prophylaxis, depends on the acetyltransferase 2 acetylation (NAT2) phenotype. Different phenotypes of NAT2 will lead to differences in drug concentration and the risk of uncontrolled side effects, such as hepatitis, peripheral neuropathy, gastrointestinal disorders (nausea, vomiting, and stomach pain). These risks are related to the presence of mutant NAT2 alleles such as NAT2*5 (c.341T> C), *6 (c.590G> A) and *7 (c.857G> A), that reduce the N- acetyltransferase activity. Therefore, the genotyping method for NAT2 polymorphism using RFLP and Sanger sequencing was established. The method was successfully applied to determine the polymorphism of 84 TB patients. This study provides a better tool for analyzing NAT2 gene to assist clinicians in treating isoniazid